2022
DOI: 10.3389/fphar.2022.919667
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Role of Retbindin, a Metabolic Regulator in the Neural Retina

Abstract: Dysregulation of retinal metabolism is emerging as one of the major reasons for many inherited retinal diseases (IRDs), a leading cause of blindness worldwide. Thus, the identification of a common regulator that can preserve or revert the metabolic ecosystem to homeostasis is a key step in developing a treatment for different forms of IRDs. Riboflavin (RF) and its derivatives (flavins), flavin mononucleotide (FMN) and flavin adenine dinucleotide (FAD), are essential cofactors for a wide range of cellular metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Most recently a study by Zhao et al, in 2022 reported on the possible association between riboflavin deficiencies and night-time blindness. 40 This study identified a key novel retina-specific riboflavin binding protein called retbindin, this binding protein plays an important role in retaining flavin levels in the retina. Their paper suggests that those with riboflavin deficiencies clinically display nyctalopia due to cellular changes in the retina.…”
Section: Vitamin B2 (Riboflavin)mentioning
confidence: 99%
“…Most recently a study by Zhao et al, in 2022 reported on the possible association between riboflavin deficiencies and night-time blindness. 40 This study identified a key novel retina-specific riboflavin binding protein called retbindin, this binding protein plays an important role in retaining flavin levels in the retina. Their paper suggests that those with riboflavin deficiencies clinically display nyctalopia due to cellular changes in the retina.…”
Section: Vitamin B2 (Riboflavin)mentioning
confidence: 99%